PENINGKATAN KEPERCAYAAN DIRI REMAJA PENGANGGUR MELALUI KELOMPOK DUKUNGAN SOSIAL - Tina Afiatin; Budi Andayani (Jurnal Psikologi, 1998)
Self-confidence is an aspect in human life, particularly in achievement. A person with better self-confidence will be able to actualize his or her abilities, while another with lower self-confidence could be inhibited in actualizing his or her abilities.Unemployed adolescents tend to have low self-confidence because being unemployed itself is a threat to one’s security feeling. Such a condition may interrupt the development of the adolescents’ personality. Thus, such adolescents may need interventions to improve their self-confidence. The present research proposed to find out the effectiveness of group social support as a model of intervention. The subjects were 24 unemployed adolescents of Desa Tirtoadi, Mlati, Sleman. Twelve of which were assigned to theexperiment group and the other 12 to the control group.The self-confidence data was obtained three times (before, immediately, after, and one month after the intervention), using the scales of Self-Confidence and of Self-Esteem. A student-t analysis toward the gained scores shows a difference between the experiment group and control group (t = 4.29; p < 0.01).The experiment group shows significant improvement (X GIE = 25.83) while the control group shows less obvious improvement (X GIK = 1.58). It can be concluded that the intervention through group social-support is effective in improving the confidence of unemployed adolescent.